Role of autoantibodies in the pathophysiology of irritable bowel syndrome: a review - Zhang, Yu; Liao, Jiazhi; Fan, Wenjuan (Frontiers in Physiology, 2024)
Irritable bowel syndrome (IBS) is a chronic, recurrent disorder that is characterized by abdominal pain associated with defecation. IBS was previously considered to manifest without any structural alterations until the discovery of post-infection IBS. An increasing body of published evidence indicates that immune activation plays an important role in the development of IBS. Nevertheless, the pathophysiology of IBS, including mainly visceral hypersensitivity and gastrointestinal dysmotility, has not yet been explicitly elucidated. The observation of potential inflammatory degenerative neuropathy, including neuronal degeneration, spearheaded research on autoimmune responses targeting the enteric nervous system. Subsequently, several autoantibodies were detected in the sera of IBS patients, among which some were presumed to exert a pathogenic influence or be associated with the etiology of gastrointestinal dysmotility in IBS. Moreover, certain specific autoantibodies evidently served as biomarkers to facilitate the differentiation between IBS and other related diseases. Therefore, we aimed to present an overview of autoantibodies reported in the sera of IBS patients and highlight their significance in diagnosing and comprehending the pathophysiology of IBS. Consequently, we propose a therapeutic strategy from an autoimmune perspective.